2015
DOI: 10.1016/j.envres.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors affecting the long term psychological impact and deterioration of mental health in flooded households

Abstract: The long term psychological effect of the distress and trauma caused by the memory of damage and losses associated with flooding of communities remains an under researched impact of flooding. This is particularly important for communities that are likely to be repeatedly flooded where levels of mental health disorder will damage long term resilience to future flooding. There are a variety of factors that affect the prevalence of mental health disorders in the aftermath of flooding including pre-existing mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 25 publications
3
97
2
Order By: Relevance
“…It should be noted, though, that this is merely one aspect of recovery. In addition, floods can also have a large and more long-term impact on the psychological well-being of those affected [61], which needs be accounted for in policies and measures that aim at supporting the recovery process of disaster stricken areas.…”
Section: Recoverymentioning
confidence: 99%
“…It should be noted, though, that this is merely one aspect of recovery. In addition, floods can also have a large and more long-term impact on the psychological well-being of those affected [61], which needs be accounted for in policies and measures that aim at supporting the recovery process of disaster stricken areas.…”
Section: Recoverymentioning
confidence: 99%
“…As presented in Literature Review section, Liu et al (2006) found positive association between the probability for an individual to suffer from post-traumatic stress disorder and flood exposure. Similarly, Lamond et al (2015) find evidence on the significant link between mental health deterioration and the depth of flood experienced by households. * p < 0.05 ** p < 0.01 *** p < 0.001 t statistic in parentheses exposed to a flood.…”
Section: Resultsmentioning
confidence: 97%
“…Respiratory-related, as well as water, food, vector-, and airborne diseases are likely to spread amidst crowding, poor hygiene, lack of access to clean water, and lack of disease prevention measures in these centers (Kouadio et al 2012;Maryam et al 2012;Matthew et al 2016;Watson et al 2007a, b). Stress and fatigue from flood exposure and the difficult circumstances that the affected households may experience in the aftermath can also lead to psychological distress and morbidity (Carroll et al 2010;Lamond et al 2015).…”
Section: Flood Characteristics and Flood Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive societal CBA of flood risk management strategies should also include avoided intangible impacts caused by floods, like psychological impacts (Lamond, Joseph, & Proverbs, ). However, intangible impacts were neglected in the identified zoning CBAs, while several valuation approaches exist (Markantonis, Meyer, & Schwarze, ).…”
Section: Flood Risk Zoning Cbamentioning
confidence: 99%